2021
DOI: 10.3390/cancers13246334
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Faulty Germinal Center Reaction on the Pathogenesis of Primary Diffuse Large B Cell Lymphoma of the Central Nervous System

Abstract: Primary lymphoma of the central nervous system (PCNSL, CNS) is a specific diffuse large B cell lymphoma (DLBCL) entity confined to the CNS. Key to its pathogenesis is a failure of B cell differentiation and a lack of appropriate control at differentiation stages before entrance and within the germinal center (GC). Self-/polyreactive B cells rescued from apoptosis by MYD88 and/or CD79B mutations accumulate a high load of somatic mutations in their rearranged immunoglobulin (IG) genes, with ongoing somatic hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…BCL6 rearrangements have been observed in 17 to 38% of PCNS-DLBCL cases by FISH using the BCL6 BA probe applied to tissue sections or single cells, 2,6,10,11,[16][17][18][19] and associated with worse progression-free and overall survivals of PCNS-DLBCL patients, 10,18 potentially accounting for the poor treatment outcome in case 2. The gene is rearranged with not only IG genes but also a variety of non-IG genes, resulting from translocations with other chromosomal loci or deletions of upstream sequences, and juxtaposed to the regulatory sequences of each partner gene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…BCL6 rearrangements have been observed in 17 to 38% of PCNS-DLBCL cases by FISH using the BCL6 BA probe applied to tissue sections or single cells, 2,6,10,11,[16][17][18][19] and associated with worse progression-free and overall survivals of PCNS-DLBCL patients, 10,18 potentially accounting for the poor treatment outcome in case 2. The gene is rearranged with not only IG genes but also a variety of non-IG genes, resulting from translocations with other chromosomal loci or deletions of upstream sequences, and juxtaposed to the regulatory sequences of each partner gene.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoma cells were aseptically prepared from the excised specimens and incubated overnight in RPMI 1640 medium supplemented with 15% heat-inactivated fetal bovine serum at 37°C under a CO 2 concentration of 5%. The cells were then cultured in the presence of 0.1 μg/mL colcemid for 2 hr.…”
Section: Cytogenetic and Dna Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is important to identify more efficient and low-toxicity antitumor drugs for treatment of cervical cancer. Glaucocalyxin B (GLB) is extracted from cymbidium blue, and it exerts anti-inflammatory, antioxidant and anti-tumor effects [9]. A study has demonstrated that GLB inhibited the proliferation and apoptosis of tongue squamous cell carcinoma cells, possibly via inhibition of the activation of NF-κB signaling pathway [10].…”
Section: Discussionmentioning
confidence: 99%